213k views
3 votes
Which of the following is a solution of x^2-8x=-27

User Breedly
by
5.6k points

2 Answers

3 votes

Answer:

Step-by-step Factoring x2-8x+27

The first term is, x2 its coefficient is 1 .

The middle term is, -8x its coefficient is -8 .

The last term, "the constant", is +27

Step-1 : Multiply the coefficient of the first term by the constant 1 • 27 = 27

Step-2 : Find two factors of 27 whose sum equals the coefficient of the middle term, which is -8 .

-27

+

-1

=

-28

-9

+

-3

=

-12

-3

+

-9

=

-12

-1

+

-27

=

-28

1

+

27

=

28

3

+

9

=

12

9

+

3

=

12

27

+

1

=

28

User Kimora
by
5.1k points
1 vote

Answer:

Simplifying

x2 + 8x = -27

Reorder the terms:

8x + x2 = -27

Solving

8x + x2 = -27

Solving for variable 'x'.

Reorder the terms:

27 + 8x + x2 = -27 + 27

Combine like terms: -27 + 27 = 0

27 + 8x + x2 = 0

Explanation:

User Dan Bracuk
by
4.6k points